Comparison between clinical significance of height-adjusted and weight-adjusted appendicular skeletal muscle mass. Issue 1 (December 2017) - Furushima, Taishi; Miyachi, Motohiko; Iemitsu, Motoyuki; Murakami, Haruka; Kawano, Hiroshi; Gando, Yuko; Kawakami, Ryoko; Sanada, Kiyoshi
Abstract Background This study aimed to compare relationships between height- or weight-adjusted appendicular skeletal muscle mass (ASM/Ht2 or ASM/Wt) and risk factors for cardiometabolic diseases or osteoporosis in Japanese men and women. Methods Subjects were healthy Japanese men (n =  583) and women (n =  1218). The study population included a young group (310 men and 357 women; age, 18–40 years) and a middle-aged and elderly group (273 men and 861 women; age, ≥41 years). ASM was measured by dual-energy X-ray absorptiometry. The reference values for class 1 and 2 sarcopenia in each sex were defined as values one and two standard deviations below the sex-specific means of the young group, respectively. Results The reference values for class 1 and 2 sarcopenia defined by ASM/Ht2 were 7.77 and 6.89 kg/m2 in men and 6.06 and 5.31 kg/m2 in women, respectively. The reference values for ASM/Wt were 35.0 and 32.0% in men and 29.6 and 26.4% in women, respectively. In both men and women, ASM/Wt was negatively correlated with higher triglycerides (TG) and positively correlated with serum high-density lipoprotein cholesterol (HDL-C), but these associations were not found in height-adjusted ASM. In women, TG, systolic blood pressure, and diastolic blood pressure in sarcopenia defined by ASM/Wt were significantly higher than those in normal subjects, but these associations were not found in sarcopenia defined by ASM/Ht2 . Whole-body and regional bone mineral density in sarcopenia defined by ASM/Ht2 were significantly lower than those in normal subjects, but these associations were not found in sarcopenia defined by ASM/Wt. Conclusions Weight-adjusted definition was able to identify cardiometabolic risk factors such as TG and HDL-C while height-adjusted definition could identify factors for osteoporosis.